AB0360 Comparative study of the characteristics of spanish and european patients in a local registry of patients with rheumatoid arthritis. (23rd January 2014) - Santos-Ramírez, C.; Rosas, J.; Senabre, J.; Santos-Soler, G.; Barber, X.; Salas, E.; Sánchez-Barrioluengo, M.; Llahí, N.; Cano, C.
Abstract : Objectives: To evaluate the characteristics of patients in a local registry of patients with rheumatoid arthritis, according to their nationality. Methods: We analyzed data from 303 patients from a local registry of patients with rheumatoid arthritis (RA) diagnosed from January 2006 to December 2011, in the Rheumatology department, Hospital Marina Baixa. Epidemiological data, analytical, clinical, disease activity, presence of erosions, duration, treatment, complications and quality of life questionnaires were collected. An analysis of clinical characteristics of patients by establishing two main comparison groups: Spanish and non-Spanish European was done. Results: We included 303 patients: 225 (74%) are Spanish, 51 are non-Spanish Europeans (17%) of which about half are of British origin, 15 (5%) are American, four (1.5%) Asian and 6 (2%) from Africa. We compared the following characteristics of the Spanish population front to the European: women 66.6% vs 66.6%. Mean age: 63.8 vs 61 years. Mean age at diagnosis: 57 vs. 52 years. Alcohol 6% vs 13%. Smokers 19% vs. 40% (p<0.05). Mantoux positive in 24% vs 9% (p=0.2). Active workers 32% vs 56%. Mean body mass index 29 vs 22 (p<0.05). Rheumatoid factor positive in 40% vs 58% (p<0.05). Citrullinated peptide antibodies positive in 40% vs 55%. Mean time of evolution: 2.3 vs 2.8 years. Inflammatory activity levels in 2011 are similar in both groups presenting a mean DAS28-ESR 2.6 in the Spanish group and 2.9 in the European group. Regarding the time from diagnosis to initiation of a disease modifying medication, the mean in the Spanish group is 3.9 months vs 5.5 months in the group of Europeans. From diagnosis to the start of a biological treatment, the mean time is 23 months vs 33 months. The use of biological drugs is similar between both groups: 21% vs 23%. Conclusions: 1. 17% of the patients in our local registry of patientswith rheumatoid arthritis is European (not Spanish). 2. The Mantoux test is positive in a higher percentage in the Spanish patients (24% vs 9%). 3. There are no differences in RA activity in both groups. 4. Europeans take an average of 1 year more from diagnosis to the beginning of a biological agent. Disclosure of Interest: C. Santos-Ramírez Grant/Research support from: Asociaciόn para la Investigaciόn en Reumatología de la Marina Baixa (AIRE-MB), J. Rosas: None Declared, J. Senabre: None Declared, G. Santos-Soler: None Declared, X. Barber: None Declared, E. Salas: None Declared, M. Sánchez-Barrioluengo: None Declared, N. Llahí: None Declared, C. Cano: None Declared